2014
DOI: 10.1186/2041-9139-5-29
|View full text |Cite
|
Sign up to set email alerts
|

History of a prolific family: the Hes/Hey-related genes of the annelid Platynereis

Abstract: BackgroundThe Hes superfamily or Hes/Hey-related genes encompass a variety of metazoan-specific bHLH genes, with somewhat fuzzy phylogenetic relationships. Hes superfamily members are involved in a variety of major developmental mechanisms in metazoans, notably in neurogenesis and segmentation processes, in which they often act as direct effector genes of the Notch signaling pathway.ResultsWe have investigated the molecular and functional evolution of the Hes superfamily in metazoans using the lophotrochozoan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 94 publications
(147 reference statements)
0
36
0
1
Order By: Relevance
“…(2012), also fell into Group D and we include it here in table 1. Group E genes encode a hairy/orange domain as well as the bHLH domain and include the Hey and Hes families, with well-defined roles in Notch signaling, as well as the more recently described Clockwork orange gene family which is absent from H. sapiens and other vertebrates (Gyoja and Satoh 2013), and a fourth gene family known as Heylike ( HeyL ) or HELT (Gazave et al. 2014; Gyoja 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012), also fell into Group D and we include it here in table 1. Group E genes encode a hairy/orange domain as well as the bHLH domain and include the Hey and Hes families, with well-defined roles in Notch signaling, as well as the more recently described Clockwork orange gene family which is absent from H. sapiens and other vertebrates (Gyoja and Satoh 2013), and a fourth gene family known as Heylike ( HeyL ) or HELT (Gazave et al. 2014; Gyoja 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic trees focused on the Group E genes have previously proven insufficiently supported to convincingly determine whether this reflects common ancestry or parallel cluster evolution, though some lineage-specific tandem duplication is supported for some species (Minguillon et al. 2003; Gazave et al. 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Notch is also expressed in teloblasts and blast cells, and functional studies revealed that the disruption of the Notch / hairy signaling results in a disruption of segmentation (Song et al 2004 ;Rivera and Weisblat 2009 ). For Platynereis dumerilii , 15 hairy paralogs could be identifi ed, which are expressed in mesodermal tissue, forming segments, and during neurogenesis, where it may be involved in the patterning of the nervous system (Gazave et al 2014 ). However, these authors also found no overlap with the expression of Notch .…”
Section: Segmentationmentioning
confidence: 95%
“…Further evidence of a common, and likely homologous, molecular profile comes from expression of the homeodomain gene Arx, the zinc finger Zic, and components of the Notch signaling pathway. These genes are expressed at each chaetae sac territory in the Platynereis larva (62,64), in C. teleta (63,65), and also in the region of the forming chaetae sac territories in T. transversa (Fig. 6 A-L and Fig.…”
Section: Recruitment Of Hox Genes For Patterning Lophotrochozoan Chaetaementioning
confidence: 99%
“…Brachiopods and annelids share the expression of lab and Post1 in the chaetal sacs (26,43,61). To further analyze these molecular similarities, we identified and studied the expression of the homeodomain-containing transcription factor Arx, the zinc finger Zic, and components of the Notch signaling pathway, all of which are associated with the development of chaetae in annelids (62)(63)(64)(65). Arx was specifically expressed in the developing and mature chaetal sacs (Fig.…”
Section: Expression Of Arx Zic and Notch Components In Brachiopod Cmentioning
confidence: 99%